The Impact of Duha Prayer and Al-Ma'surat Reading on Increasing Student Grades - Garnis Al Widyatri; Atiqa Sabardila (Tarbiyah Departement collaboration with AMCA, 2023)
This article explores the impact of dhuha prayer religious activities on increasing student scores at SMP IT Insan Mulia Pati. The religious program carried out in which the Dhuha prayer in congregation and the reading of Al-Ma'surat are also carried out. Regarding the selection of SMP IT Insan Mulia Pati as the object of this research, because at the school it has become a routine activity that must be carried out as a daily education program. This study uses qualitative analysis techniques and data collection. The researcher used a qualitative method of collecting data and analysis by emphasizing the qualitative descriptive method. The purpose of this study (1) is to find out the values that can be contained in the implementation of the religious activities of praying dhuha and reading al ma'surat at SMPIT Insan Mulia, (2) knowing that these religious activities can affect student achievement, (3) knowing that these activities can increase the value of emotional intelligence of students in religious activities of Duha prayer and Al Ma'surat reading, (4) knowing supporting activities other than religious activities Duha prayer and Al Ma'surat reading.